Feedback environment: A meta‐analysis. (22nd September 2021) - Katz, Ian M.; Rauvola, Rachel S.; Rudolph, Cort W.
Abstract: Feedback environment reflects the perceptions of the contextual, day‐to‐day feedback process within supervisor–subordinate relationships. Here, we present a comprehensive meta‐analysis of the feedback environment literature. On the basis of K = 112 independent samples, representing N = 31, 089 workers, results suggest that feedback environment is positively related to feedback orientation ( r c = .42), leader–member exchange ( r c = .81), supervisor‐rated performance ( r c = .29), and negatively related to burnout ( r c = −.51). Moreover, we present multiple regression and relative weights analyses to consider the unique and incremental predictive power of feedback environment above and beyond two related constructs: leader–member exchange and feedback orientation. The results suggest that the feedback environment explains unique variance in several correlates and is a particularly important predictor of (lower) burnout. Practitioner points: Positive feedback environments are important components of healthy supervisor‐suboridnate relationships. Feedback environments are instrumental in facilitating wellbeing at work, incremental to LMX and feedback orientation. Feedback environment is not a panacea for performance or other organizationally relevant correlates.